2022
DOI: 10.3390/ma15041471
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Cleaning of Magnetite Deposits on the Flow Mini-Channels of a Printed Circuit Heat Exchanger in an EDTA-Based Solution

Abstract: The dissolution behavior of magnetite deposited on flow mini-channel surfaces within a printed circuit heat exchanger (PCHE) and the corrosion behavior of a STS 316L PCHE material were investigated in an ethylendiaminetetraacetic acid (EDTA)-based chemical cleaning solution at 93 °C. The fouling in the PCHE was simulated using a water-steam circulation loop system. Most of the magnetite deposits were rapidly dissolved in the early stage of the circulation chemical cleaning. An empirical equation for estimating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Lee and Sung [30] showed that the corrosion rate of Alloy 600 was extremely low (maximum 2.3 mils) and was within the EPRI recommendation (<10 mils). Han et al [31] found that the corrosion rate of stainless steel 316L was very low in a 20% EDTA-based cleaning solution. In this work, except for Fe, the Cr and Ni elements were not detected in the ICP-OES results.…”
Section: Microstructural Analysis and Amount Of Magnetite Depositsmentioning
confidence: 99%
“…Lee and Sung [30] showed that the corrosion rate of Alloy 600 was extremely low (maximum 2.3 mils) and was within the EPRI recommendation (<10 mils). Han et al [31] found that the corrosion rate of stainless steel 316L was very low in a 20% EDTA-based cleaning solution. In this work, except for Fe, the Cr and Ni elements were not detected in the ICP-OES results.…”
Section: Microstructural Analysis and Amount Of Magnetite Depositsmentioning
confidence: 99%
“…The condition of the inner surface of the mini-channel is important. Factors influencing the surface condition are roughness [8] and fouling [9]. Another issue is the type of heat transfer fluid: gas or liquid, single-phase or two-phase fluid flow [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%